The protective action of ethanolic stem bark extract of Carissa edulis (VAHL) Apocynaceae against carbon tetrachloride Hepatotoxicity in rats - Y. Izam, Y.; B. Bukar, B. (International Journal of Pharmacology and Toxicology, 2021)
Background: Carissa edulis is generally used for the treatment of diverse ailments, but little or no interest has been shown on its hepatoprotective properties. This research work was aimed at evaluating the safety and claimed hepatoprotective activity of Carissa edulis.Method: For the intent of data collection, the method of Li et al., 2011 was used. In this method animals were treated with (250,500 and 1000mg/kg) of stem bark extract. The extract was given daily by gavage to the animals for 28 consecutive days. The 50% v/vCCl4 and olive oil was gavaged through gastric tube twice a week. The tests conducted were liver function test, liver antioxidant enzymes test, lipid profile test as well as Histopathological assessment of the liver sections.Results: Results of the study revealed that the markers in the animal treated with CCl4 were significantly higher than the normal control at (P<0.05). While blood samples from animals treated with the stem bark extracts were significantly lower than the CCl4 group at (P<0.05).Conclusion: These results imply that the ethanolic stem bark extract of Carissa edulis have a protective effect against CCl4 induced hepato - cellular injury.Â Â Â